Public knowledge, attitudes and self-practice towards diabetes mellitus in Kangar, Perlis - Soo, Pei Pei; Dali N,; Shakar NS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
In Malaysia, the prevalence of diabetes mellitus (DM) was the second highest in Perlis. Prevention and management of DM are largely dependent on self-care in our daily lives. Nonetheless, we have little information concerning factors influencing public engagement in DM self-practice, which might have contributed to the high prevalence of DM in Perlis. This study was conducted to evaluate knowledge, attitudes, and factors associated with self-practice towards DM among the public in Kangar, Perlis. A cross-sectional study was conducted in June 2018 for three months. Eligible participants were invited to complete a self-administered questionnaire in public areas in Kangar. Descriptive analyses on the sociodemographic, medical backgrounds, knowledge, attitudes, and self-practice towards DM were performed. Independent t-test and Spearman’s correlation were performed to assess the association between sociodemographic characteristics, medical history, knowledge, and attitudes with self-practice towards DM. Multiple linear regression was used to adjust for potential confounding variables. A total of 319 respondents consented and participated in this study. Most of the respondents were female (66.5%), Malay (94%), and had tertiary education (51.7%). Overall, most participants had good scores on knowledge (80.3%), attitudes (98.4%), and self-practice (97.2%) towards DM. A statistically significant positive association was found between age, education level, and attitudes score with DM self-practice (p<0.05). This study suggests a well-structured educational program on diabetes self-care should start as early as in school to clarify public misconceptions on DM management.